2013
DOI: 10.3389/fphar.2013.00006
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Antibody Analysis of Pannexin1 Expression in Four Rat Brain Regions Reveals Varying Subcellular Localizations

Abstract: Pannexin1 (Panx1) channels release cytosolic ATP in response to signaling pathways. Panx1 is highly expressed in the central nervous system. We used four antibodies with different Panx1 anti-peptide epitopes to analyze four regions of rat brain. These antibodies labeled the same bands in Western blots and had highly similar patterns of immunofluorescence in tissue culture cells expressing Panx1, but Western blots of brain lysates from Panx1 knockout and control mice showed different banding patterns. Localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 107 publications
8
33
0
1
Order By: Relevance
“…However, due to poor specificity of most available antibodies against this protein [22], quantitative immunohistochemistry data for Panx1 remains rather unreliable. Here, we addressed this concern by alternative, more quantitative approach, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to poor specificity of most available antibodies against this protein [22], quantitative immunohistochemistry data for Panx1 remains rather unreliable. Here, we addressed this concern by alternative, more quantitative approach, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Many of these antibodies are extensively used in the literature, but readers of a particular article have no way of knowing that concerns have been raised. We have similar examples with software tools 3 , data sets 1, 5 and genetically modified animals 2 . We have an infrastructure in place, CrossMark, to alert readers of a particular article that an addendum or erratum has been posted.…”
Section: Discussionmentioning
confidence: 99%
“…In the hippocampus, high Panx1 expression was found in GABAergic and glutamatergic neurons within the dentate gyrus and all CA regions, stratum oriens, stratum radiatum, and stratum lacunosum-moleculare [28]. Although the initial studies showed no overlap of Panx1 with the astrocyte marker GFAP in the brain, recent work by the Sosinsky group reported Panx1 staining in astrocytes using a variety of different Panx1 antibodies thus far developed [31]; this study corroborates other in vivo and in vitro evidence for Panx1 expression in astrocytes [3236]. …”
Section: Distribution Of Pannexins In the Nervous Systemmentioning
confidence: 99%